Trade-off analysis of C12A7:e− deposition techniques applied to Low Work Function Tethers. (December 2020) - Fabian-Plaza, Jose; Meiro, Gerardo; Post, Angel; Pérez-Casero, Rafael; Palomares, F. Javier; Tejedor, Paloma; Naghdi, Samira; Várez, Alejandro; Sánchez-Arriaga, Gonzalo
Abstract: Due to its extraordinary properties, the C12A7:e − electride has been suggested in the past as one of the most promising materials for coating Low Work-function Tethers (LWTs). Such subclass of electrodynamic tether, made of a conductive substrate coated with materials that enhance the electron emission through the thermionic and photoelectric effects, would constitute a fully passive and consumable-free device for deorbiting space debris from Low Earth Orbit. This work presents experimental results on the manufacturing and testing of small tape-like LWT samples, which is the relevant geometry for electrodynamic tether applications. After preparing C12A7:e − targets under specific and controlled conditions, thin titanium foils have been coated with the C12A7:e − electride by using two different physical vapor deposition techniques: magnetron sputtering (MS) and pulsed laser deposition (PLD). In the case of MS, important difficulties and defects were found, including target damage, poor growth rate, and oxidation and changes in the composition of the coating. However, the performance on the PLD coating was radically different. First, Rutherford backscattering spectrometry confirmed that the composition of the thin film with the PLD coincides with that of the target. Second, X-ray photoelectron spectroscopy and thermionic emission experiments showed that the work function of the LWT sample is 2.6 ± 0.1 eV. Therefore, the trade-off analysis indicates that PLD can be used to manufacture LWT samples with work function close to the one of the bulk C12A7:e − (2.4 eV). Nevertheless, its application as passive cathode in electrodynamic tethers still requires further research activities. Highlights: Low Work-function Tethers (LWT) is a conductive tape coated with a low work function materials. Synthesizing C12A7:e−as low work function materials. Depositing the synthesized C12A7:e−on a thin titanium foil by using a pulsed laser deposition technique (PLD). The PLD technique has proved successful at preserving the chemical composition of the target in the deposited films. The obtained work function of C12A7:e−coated thin titanium foil is 2.6 ± 0.1 eV.